Translocator protein–mediated fast-onset antidepressant-like and memory-enhancing effects in chronically stressed mice. (April 2020) - Shang, Chao; Yao, Ru-Meng; Guo, Ying; Ding, Zhen-Chun; Sun, Li-Jun; Ran, Yu-Hua; Xue, Rui; Wang, Huai-Shan; Zhang, Jian-Min; Zhang, You-Zhi; Zhang, Li-Ming; Li, Yun-Feng
Background: Fast-acting and cognitive-enhancing antidepressants are desperately needed. Activation of translocator protein (18 kDa, TSPO) is a novel strategy for developing potential antidepressants, but there are no data available on the onset time of TSPO ligands. This study aimed to investigate the fast-onset antidepressant actions of AC-5216, a selective TSPO ligand, in TSPO knock-out (KO) mice. Methods: TSPO wild-type (WT) and KO mice were subjected to a six-week chronic unpredicted stress (CUS) paradigm. Then, the mice were treated with AC-5216 and tested with depressive and cognitive behaviours. Results: A single dose of AC-5216 (0.3 mg/kg) exerted anxiolytic- and antidepressant-like actions in TSPO WT mice. Moreover, in chronically stressed WT mice, two to four days of AC-5216 treatment (0.3 mg/kg, once per day) produced fast-onset antidepressant-like effects in the novelty-suppressed feeding and sucrose preference tests, as well as memory-enhancing effects in the novel object recognition test. In addition, a rapid (with five days of treatment) restoration of serum corticosterone levels and prefrontal cortex (PFC) allopregnanolone levels was found. Further studies showed that in these stress-exposed WT mice, AC-5216 significantly increased the levels of mTOR signalling-related proteins (mBDNF, p-mTOR, PSD-95, synapsin-1, GluR1), as well as the total dendritic length and branching points of pyramidal neurons in the PFC. Conclusions: These results suggest that TSPO mediates the fast-onset antidepressant-like and memory-enhancing effects of AC-5216, possibly through the rapid activation of mTOR signalling and restoration of dendritic complexity in the PFC.